Biotechnology concepts, methodologies, tools, and applications (IGI Global, 2019)
"This book is a vital reference source for the latest research findings on the application of biotechnology in medicine, engineering, agriculture, food production, and other areas. It also examines the economic impacts of biotechnology use"--Provided by publisher.